PENATALAKSANAAN TERAPI RELAKSASI OTOT PROGRESIF DALAM MENURUNKAN SKALA NYERI SENDI PADA LANSIA ASAM URAT DI PANTI SOSIAL HARAPAN KITA PALEMBANG TAHUN 2021 - Octarina Piko, Sari; Sandro , Ray (JURNAL SMART ANKes, 2023)
Gout is one of the most common inflammatory joint diseases characterized by the accumulation of Monosodium urate crystals in and around the joints. One of the treatments for Gout Arthritis is with progressive muscle relaxation techniques. Progressive muscle relaxation techniques are one technique for reducing muscle tension with a simple and systematic process of tensing a group of muscles and then relaxing them again. Progressive muscle relaxation techniques can reduce pain, anxiety and depression, thereby improving sleep quality and reducing fatigue. The purpose of this Scientific Paper is to find out an overview of the management in reducing the Joint Pain Scale in the Elderly with Gout. The research design is Descriptive with the Case Study method. The implementation of Progressive Muscle Relaxation Therapy in the elderly was carried out at the Harapan Kita Social Home in Palembang from August 9, 2021 to August 11, 2021. The subjects of this study were 2 elderly people suffering from Gout. The planning provided for the Management of Progressive Muscle Relaxation Therapy in Reducing the Joint Pain Scale in the Elderly with Gout. Data collection instruments are chairs with backrests, pillows, uric acid test tools, stationery, watches with seconds, cellphones to play music and geriatric nursing care formats. Research after progressive muscle relaxation therapy for 3 days, both elderly people experienced a decrease in uric acid levels and joint pain scales. Uric Acid Levels in Mr. "S" before progressive muscle relaxation therapy were 10.4 mg/dl while the joint pain scale was 6 and after progressive muscle relaxation therapy was 5.6 mg/dl while the joint pain scale was 1. While in Mrs. "H" before progressive muscle relaxation therapy was 9.3 mg/dl while the joint pain scale was 4 and after progressive muscle relaxation therapy was 5.6 mg/dl while the joint pain scale was 0. After progressive muscle relaxation therapy for 3 days, both elderly people experienced a decrease in uric acid levels and joint pain scales.